Groups of finite non-Abelian sectional rank - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study non-Abelian locally finite groups and non-Abelian locally solvable groups of finite non-Abelian sectional rank and prove that their (special) rank is finite.